COULD THE NEUTROPHIL/LYMPHOCYTE RATIO BE AN ALTERNATIVE MARKER FOR THE PREDICTION OF INSULIN RESISTANCE IN PREDIABETIC PATIENTS?: A RETROSPECTIVE STUDY - Durmuş Ayan; Kader Zeybek Aydoğan; Tevfik Balcı; Esma Özmen; Umut Karabay (Sabiad)
Objective: In our study, we aimed to compare Triglyceride/Glucose (TyG) index, LDL-C/HDL-C ratio, Triglyceride/HDL-C ratio, and Neutrophil/ Lymphocyte Ratio (NLR) with the HOMA-IR index in non-diabetes and prediabetes. Material and methods: A total of 1433 patients were included 673 women, and 890 men, aged between 18-75 years, applied to Niğde Ömer Halisdemir University Training and Research Hospital between 2019-2021 in our study. HOMA-IR index, TyG index, LDL-C/HDL-C ratio, Triglyceride/ HDL-C ratio, and NLO values were calculated by means of the analyzed tests. Results: According to our findings, the sensitivity and specificity of the Triglyceride/HDL-C ratio in the non-diabetic group and the NLR in the prediabetic group were higher than the routinely used method, the HOMA-IR index, as well as other indexes used in IR estimation. In addition, while a positive significant correlation was found between the Triglyceride/HDL-C ratio and the HOMA-IR index in the non-diabetic group (r=0.219; p<0.001), there was no significant correlation between NLR and HOMA-IR index in the pre-diabetic group (r=0.219; p<0.001), r=0.034; p=0.290). Conclusion: NLR may be an alternative parameter to predict IR in prediabetic patients. However, we think that there is a need for prospective studies that are verified by the reference method.